2008
DOI: 10.5194/bg-5-693-2008
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characteristics and bacterial community structure of the sea surface microlayer in the South Pacific Ocean

Abstract: Abstract. The chemical and biological characteristics of the surface microlayer were determined during a transect across the South Pacific Ocean in October-December 2004. Concentrations of particulate organic carbon (1.3 to 7.6-fold) and nitrogen (1.4 to 7-fold), and POC:PON ratios were consistently higher in the surface microlayer as compared to surface waters (5 m). The large variability in particulate organic matter enrichment was negatively correlated to wind speed. No enhanced concentrations of dissolved … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 53 publications
9
57
1
Order By: Relevance
“…5B). Similarly, Obernosterer et al (2008) found particulate organic matter enrichment in the microlayer was negatively correlated with wind speed. The SSM at Sta.…”
Section: Discussionmentioning
confidence: 99%
“…5B). Similarly, Obernosterer et al (2008) found particulate organic matter enrichment in the microlayer was negatively correlated with wind speed. The SSM at Sta.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that most of recent studies on bacterial abundance at the SML used flow cytometry (instead of microscopy) for cell counting (e.g. Agogué et al 2005a, Joux et al 2006, Obernosterer et al 2008, Stolle et al 2010, where inclined indiscriminate detection of particle-attached bacteria (Obernosterer et al 2005), may have resulted in lower EFs. Although to the best of our knowledge there are only 8 published studies that reported flagellate numbers in the SML, the EFs of hetero (HF)-and autotrophic flagellates (AF) in our HCC site (22.6 and 18.8, respectively) were the highest among the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has shown that the SML contains elevated concentrations of heterotrophic-and autotrophic micro organisms including bacteria, cyanobacteria, flagellates and algae (e.g. Taguchi & Nakajima 1971, Sieburth et al 1976, Harvey & Young 1980, Garabét-ian 1990, Agogué et al 2004, Obernosterer et al 2008, Santos et al 2011. Concentrations of these microorganisms are generally 1 to 10 times greater at the SML than in the sub-surface water (SSW) ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Tilstone et al (2010) suggested that microbial production of CDOM, including FDOM, occurs within a welldefined SML, and that CDOM may act as UV-protection for phytoplankton within the SML. Similarly, Obernosterer et al (2008), who performed their study in a nonupwelling region, reported constant CDOM enrichment in the SML at six stations in the tropical Pacific, providing additional evidence that continuous supply of CDOM to the SML, either from the bulk water or through microbial production in the SML, balances out losses due to photobleaching at extremely high solar and UV irradiance.…”
Section: Discussionmentioning
confidence: 99%
“…Organic materials are transported upward from bulk water to the SML through diffusion, positively buoyant particles (Azetsu-Scott and Passow, 2004), and rising air bubbles (Gershey, 1983). In addition to the direct net production of organic matter within the SML (Wurl et al, 2016), upward transport of organic matter from bulk water explains the typical enrichment of organic matter in the SML (Obernosterer et al, 2008). Our observations of elevated EFs during upwelling indicate the ability of upwelled water masses to capture by-products of biological processes from the euphotic zone of the water column.…”
Section: Discussionmentioning
confidence: 99%